2009
DOI: 10.1128/iai.00967-08
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Inflammation and Apoptosis in Improved Survival in a Model of Hyperoxia-Induced Acute Lung Injury inPneumocystis murina-Infected Mice

Abstract: Pneumocystis infections increase host susceptibility to additional insults that would be tolerated in the absence of infection, such as hyperoxia. In an in vivo model using CD4-depleted mice, we previously demonstrated that Pneumocystis murina pneumonia causes significant mortality following an otherwise nonlethal hyperoxic insult. Infected mice demonstrated increased pulmonary inflammation and alveolar epithelial cell apoptosis compared to controls. To test the mechanisms underlying these observations, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…These authors demonstrated that synthetic double-stranded small interfering RNA (siRNA) targeting FADD introduced into the tissues of the whole animal suppressed apoptosis induction in septic lungs, prevented acute lung injury development, and dramatically improved the survival of CLP mice (65). A similar critical role of epithelial cell apoptosis via activation of the Fas/FasL pathway has been also described in a model of hyperoxia-induced acute lung injury in Pneumocystis murina -infected mice (66). These observations support the hypothesis that apoptosis of alveolar epithelial cells potentially through the Fas/FasL pathway is involved in the pathophysiology of acute lung injury and pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…These authors demonstrated that synthetic double-stranded small interfering RNA (siRNA) targeting FADD introduced into the tissues of the whole animal suppressed apoptosis induction in septic lungs, prevented acute lung injury development, and dramatically improved the survival of CLP mice (65). A similar critical role of epithelial cell apoptosis via activation of the Fas/FasL pathway has been also described in a model of hyperoxia-induced acute lung injury in Pneumocystis murina -infected mice (66). These observations support the hypothesis that apoptosis of alveolar epithelial cells potentially through the Fas/FasL pathway is involved in the pathophysiology of acute lung injury and pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…ATII cells were isolated as described 21,45 . Briefly, perfused and lavaged lungs were digested with dispase (1 ml, BD Bioscience) and purified by negative immunoselection using a mixture of antibodies, including anti-CD16/32 (2.4G2, BD Biosciences), anti-TER-119 (TER-119, BD Biosciences), anti-CD45 (30-F11, BD Biosciences), and anti-CD90 (OX-7, BD Biosciences), followed by differential adherence to dishes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this role in host defense, GM-CSF is a mitogen for AEC in vivo and in vitro (22,32). Using exposure to increased concentrations of oxygen to induce lung injury, we have found that GM-CSF is protective against lethal lung injury both in normal mice (32) and in mice rendered more susceptible to lung injury by infection with Pneumocystis murina (4). In these experiments, treatment with GM-CSF or overexpression of GM-CSF in the lung was associated with decreased apoptosis of AEC following exposure to hyperoxia.…”
mentioning
confidence: 96%